Understanding the Patterns and Trends of Food Consumption in a Developing Country Context: The Case of Amhara Region, Ethiopia - Mengesha ST (Dove Medical Press, 2021)
Seyoum Teffera Mengesha Department of Economics, College of Business and Economics, Bahir Dar University, Bahir Dar, EthiopiaCorrespondence: Seyoum Teffera MengeshaDepartment of Economics, College of Business and Economics, Bahir Dar University, PoBox: 618, Addis Alem, Bahir Dar, EthiopiaEmail Seyoum.Teffera@bdu.edu.etBackground: Food and nutrition security continued to be a significant concern in the global food system. However, this system is not delivering optimal nutrition and health outcomes. Most low- and middle-income countries are burdened by persistent undernutrition and recently growing overweight and diet-related non-communicable diseases. One of the mechanisms for addressing this nutrition paradox is understanding consumers’ food choices and preferences. Thus, this study’s objective was to assess the patterns and trends of food consumption in a developing country context: the case of Amhara region, Ethiopia, and to identify market-based interventions involving specific foods and groups.Methods: A household-based cross-sectional study and multistage sampling technique were used to select study participants and collect data. A structured questionnaire was used for data collection, and the study adopted a descriptive research approach and a mix of complementary qualitative and quantitative methods in its analysis. A Household Dietary Diversity Score (HDDS) to describe the respondents’ food consumption pattern was used in the study.Results: Following FAO (2010)’s guideline, the HDDS score was calculated based on the intake of 12 food groups using a week recall data. The average HDDS was 8.5 out of 12 food groups. The average HDDS was relatively high, which might be related to the week recall in our data measurement period.Conclusion: This report seeks to understand consumers’ behavior by investigating several aspects of food choices, including household dietary diversity and food expenditures. The study also provides insights for researchers to further investigate the issue by adding other scientific databases and methods to draw more meaningful and implementable conclusions.Limitations: Although the sampling procedure was random, it might not be representative to study the patterns and trends of food consumption at a country or broad level due to its small size.Keywords: food consumption, HDDS, nutrition, Ethiopia